Toward Improvement of Resistance Testing Reliability - Utama, I Ketut Aria Pria; Purnamasari, Dian; Suastika, I Ketut; Nurhadi, Nurhadi; Thomas, Giles Anthony (Journal of Engineering and Technological Sciences, 2021)
Periodically conducting a benchmark test with estimated uncertainty is important to improve the quality of resistance predictions and understand the influence of instrumentation, testing procedures and analysis techniques. The LHI-007 Ro-Ro Ferry ship model, made available by the Maritime Research Institute Netherlands (MARIN), was used for benchmark testing from 2010 to 2018 at the Indonesian Hydrodynamic Laboratory. Comparisons were made between filtering the resistance data with a low-pass filter and with a Kalman filter. This work shows how benchmark tests can be used to track test performance over a longer period and proposes techniques to improve the uncertainty in the resistance results.